Fecal microbiota transplantation: a novel strategy and challenges in the adjuvant treatment of bladder Cancer - Liu, Xinwei; Chen, Zhiqiang; Lu, Yichen; Wu, Yifan; Huang, Yongneng; Zhang, Yuwei; Li, Menglu; Feng, Ninghan (Frontiers in Microbiology, 2026)
The clinical management of bladder cancer faces major challenges due to treatment resistance and recurrence, which require the development of new adjuvant strategies. The role of the gut microbiome in influencing bladder cancer progression and treatment response through the “gut-bladder axis” is gaining recognition. This understanding provides a theoretical rationale for exploring microbiota-targeting interventions, such as fecal microbiota transplantation (FMT). As a method capable of thoroughly reshaping the gut microbiota, FMT may have broad clinical potential. This review systematically explores the possible role of FMT in treating bladder cancer. It begins by summarizing the observational and causal evidence linking gut microbiota dysbiosis to bladder cancer, which forms the rationale for considering FMT as an intervention. Then, it discusses how FMT might improve therapeutic effectiveness, including regulation of microbial metabolites (such as short-chain fatty acids, tryptophan, and bile acids), repair of the intestinal barrier, induction of epigenetic reprogramming and modulation of the urinary microbiota. The review also considers potential scenarios for combining FMT with existing adjuvant therapies, including immunotherapy, chemotherapy, and radiotherapy. Finally, it objectively evaluates the key challenges in translating FMT into clinical practice, including effectiveness, safety, standardization, and regulatory or ethical issues, and outlines future directions. By synthesizing current evidence, this review highlights FMT as a potentially promising and innovative adjuvant strategy worthy of further investigation, which, if validated, could contribute to overcoming current therapeutic challenges in bladder cancer.